Dakwah di Balik Algoritma: Analisis Echo Chamber dan Filter Bubble dalam Pembentukan Opini Publik terhadap Kasus Ustadz di Pati - Hendra Prasetia; Ikbal Nursamsi; Asep Iwan Setiawan (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2026)
Religious digitalization has shifted the dawah stage from traditional pulpits to visual-interactive platforms mediated by algorithms. This study aims to analyze how the mechanisms of Filter Bubbles and Echo Chambers on Instagram social media shape Indonesian netizens' public opinion, specifically in responding to moral scandals involving religious authorities in Pati Regency. Using a qualitative research method with a netnographic approach, the researcher conducted passive observation (lurking) of organic interactions in Instagram comment columns. The results show that the Instagram algorithm creates information isolation that reinforces confirmation bias among loyalists, but simultaneously triggers destructive polarization when the scandal penetrates public information bubbles. These findings identify four dominant narrative typologies: institutional delegitimization, dogmatic sarcasm, negative generalization, and demands for mass justice. This study concludes that digital dawah under algorithmic control creates new vulnerabilities for religious authorities, where radical social media transparency can instantly collapse institutional reputation through the phenomenon of Cyber-Balkanization.